The Influence of Work Motivation on Indomaret Employee Performance - Mohadi Hilmi; Muhammad Nurul Ashab; Nana Sari (Global Sustainability Research Institute, 2024)
Introduction: This research aims to investigate the influence of motivation on employee performance at the Indomaret retail company. As a leading company in the retail industry in Indonesia, employee performance at Indomaret is an important factor in maintaining competitiveness and meeting dynamic market demands. The concept of motivation, which has long been a focus of attention in the human resource management literature, plays an important role in shaping employee behavior and productivity. Methods: Data collection was carried out offline by distributing questionnaires to Indomaret employees in Malang. The number of research samples used purposive techniques and a sample of 32 samples was obtained. The research data analysis method uses simple linear regression, then the research instrument is tested using product moment for validity testing and Cronbach's alpha for reliability testing. Results: The results of this research show that work motivation has a positive effect on employee performance. Conclusion and suggestion: It is hoped that the results of this research can provide concrete input for Indomaret management in designing more effective employee motivation policies. It is also hoped that these findings can contribute to human resource management literature, especially in the context of the retail industry in Indonesia. In addition, it is hoped that this research can pave the way for further, more in-depth research regarding motivation strategies that can improve employee performance in the competitive retail industry.